Introduction of standardized, cumulative quantitative measurement of blood loss into routine maternity care. (18th April 2022) - Powell, E.; James, D.; Collis, R.; Collins, P. W.; Pallmann, P.; Bell, S.
Abstract: Introduction: Postpartum hemorrhage (PPH) is the leading cause of maternal morbidity in the UK. Visual estimation of blood loss is unreliable yet remains common practice. As part of a national quality improvement project to improve care during PPH, standardized, quantitative measurement of blood loss (QBL) for all deliveries was introduced into a tertiary obstetric unit in Cardiff, Wales. Methods: Retrospective analysis of 875 consecutive maternities between December 2017 and February 2018 was undertaken. Of these, 372 mothers had both pre- and post-partum hemoglobin (Hb) were recorded. Regression analyses were performed to investigate the relationship between change in Hb adjusted for red cell transfusion and QBL. Results: The correlation coefficient between QBL and adjusted change in Hb for all deliveries ( n  = 372) was 0.57. This corresponded to an estimated fall of adjusted change in Hb of 15.3 g/L (95% CI: 13.1, 17.6) per 1000 mL blood loss. Discussion: QBL has been shown to be reliable across all maternity settings, with reproducible results in theater and delivery rooms (on the obstetric unit and alongside midwifery-led unit). QBL is moderately correlated with adjusted change in Hb for all volumes of bleeding and gives clinicians more accurate knowledge of blood loss than visual estimation. This low-cost, low-fidelity intervention can influence the timely escalation of clinical care and therefore patient outcome.